Using TikTok Media as a Tool to Asses the Improvement of Student Description Text Skills Class X - Siagian, Firstananda Jenni Yulieta; Meisuri, Meisuri (Universitas Negeri Medan, 2024)
The integration of digital media in language learning has become increasingly important in modern education. This study explores the use of TikTok as a tool to assess and improve students' descriptive text writing skills in an English as a Foreign Language (EFL) context. The research was conducted with Class X students at SMA Sultan Iskandar Muda Medan, North Sumatra, using a Classroom Action Research approach. The study involved two cycles: the first without TikTok and the second incorporating TikTok as a learning medium. Data was collected through observations, tests, and assessments of students' written and oral presentations. Results showed a significant improvement in students' descriptive writing skills when using TikTok, with higher scores in content relevance, clarity of description, and overall engagement. The study found that TikTok provided an interactive and engaging platform for students to practice their descriptive writing skills in a real-world context. This research concludes that incorporating TikTok in EFL classrooms can effectively enhance students' descriptive writing abilities and increase their motivation to learn English. The findings suggest that integrating social media platforms like TikTok can be a valuable strategy for language educators seeking to improve students' writing skills in a digital age.